Attosecond delays in photoionization studied with coherent-controlled FEL. Issue 11 (January 2020) - You, D; Ueda, K; Tugs, O; Orimo, Y; Sato, T; Ishikawa, K L; Gryzlova, E V; Staroselskaya, E I; Grum-Grzhimailo, A N; Carpeggiani, P A; Csizmadia, T; Füle, M; et al.
Synopsis: When an electron is ejected from an atom after absorption of a photon, the photoelectron wave packet has an extremely short group delay between the photon absorption and the electron emission. This interval, called the Eisenbud-Wigner-Smith delay, is on the order of a few attoseconds. Here, we present a new method to measure the photoemission delay, using coherent-controlled free-electron laser pulses.